Paraneoplastic Extralimbic Encephalitis Associated with Thymoma: A Case Report - Aragaki, Masato (Ann Thorac Cardiovasc Surg, 2015)
Here we a report a rare case of extralimbic encephalitis associated with thymoma. A 66-year-old woman was admitted to our hospital with cramping in her right leg and inability to walk. Magnetic resonance imaging of the brain showed multifocal high intensity signals on T2 flare images in the cerebral cortex, and chest computed tomography showed a 5-cm anterior mediastinal mass, which was considered to be a thymoma. We speculated that she had paraneoplastic encephalitis associated with thymoma. She underwent a thymectomy and was diagnosed with type B1 thymoma. On postoperative day 6, her neurological symptoms began to improve. On postoperative day 31, she was discharged without complications. Limbic encephalitis is a paraneoplastic neurological syndromeassociated with thymoma, but extralimbic encephalitis has been described in the literature very rarely. We report the case of extralimbic encephalitis associated with thymoma along with a literature review.